2013
DOI: 10.1159/000347059
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies for Tendon Healing Based on Novel Biomaterials, Factors and Cells

Abstract: The repair of tendon injuries still presents a major clinical challenge to orthopedic medicine. Tendons, like some other tissues, are poorly vascularized and heal slowly. In addition, healing often leads to the formation of fibrous tissue and scar tissue which lack flexibility and biomechanical properties. So the treatment of tendon injuries is challenging. We give an overview of the structure and composition of tendons, pathological states of tendon and natural healing, as well as therapeutic options. We focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…The main constituent of the tendon extracellular matrix is collagen. Collagen type I accounts for nearly 95% of the total content of the matrix, and the remaining 5% is formed from collagen types III, V, VI, XII, and XIV [5052]. Controversial studies on the effect of PRP on collagen expression in tenocytes have been reported, and in some of those studies the expression of collagen types I and III seems to be induced [35].…”
Section: Resultsmentioning
confidence: 99%
“…The main constituent of the tendon extracellular matrix is collagen. Collagen type I accounts for nearly 95% of the total content of the matrix, and the remaining 5% is formed from collagen types III, V, VI, XII, and XIV [5052]. Controversial studies on the effect of PRP on collagen expression in tenocytes have been reported, and in some of those studies the expression of collagen types I and III seems to be induced [35].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, an isoform of scleraxis (SCX), a critical transcription factor in tendon development [74], was reduced in old tendon. In addition, the reduced expression in old tendon of EGR2 and AS EGR1, both of which are required for tendon differentiation [75], may affect tendon repair [76]. …”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesised that pseudogenes act as post-transcriptional regulators of the corresponding parental gene [74]. In other studies, pseudogenes have been identified as increasing with age, such as pseudogene cyclin D2 in the ovary [76], and recent work has indicated that they may have a role in inflammation [77]. This provides an exciting new frontier to explore in ageing research, and further work is required to determine whether any of the pseudogenes identified in this study have functional significance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, donor site is the additional wound and systemic stress factor . This clinical problem might be solved by biovital skin substitutes obtained by tissue engineering methods . The essence of the method is to use elements of allogeneic dermis extracellular matrix as a scaffold for in vitro cultured autologous fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…2 This clinical problem might be solved by biovital skin substitutes obtained by tissue engineering methods. [3][4][5] The essence of the method is to use elements of allogeneic dermis extracellular matrix as a scaffold for in vitro cultured autologous fibroblasts. Insertion of a scaffold into a newly formatted tissue provides mechanical protection against in vivo occurring forces until the grafted skin substitute will become an integral element of the body.…”
Section: Introductionmentioning
confidence: 99%